Marvin: Deployment system for CoreData - Gadidjah Margrét Ögmundsdóttir 1994-; Marinó Fannar Pálsson 1981-; Sigurður Rúnar Helgason 1985- (2014)
Heildartexti lokaskýrslu. Prentuð útgáfa og öll fylgiskjöl á CD eru varðveitt á bókasafni HR. In this report we discuss a B.Sc project entitled "Marvin: Deployment system for Coredata". This work was conducted at Reykjavík University in the fall of 2014 in collaboration with Azazo. In this work we introduce a new deployment system, which we call Marvin, that will eventually be the main deployment tool for Azazo's CoreData. Azazo